Novel approach to hydroxy-group-containing porous organic polymers from bisphenol A - Wang, Tao; Zhao, Yan-Chao; Zhang, Li-Min; Cui, Yi; Zhang, Chang-Shan; Han, Bao-Hang (Beilstein Journal of Organic Chemistry, 2017)
We successfully employed bisphenol A and several different formyl-containing monomers as useful building blocks to construct a series of hydroxy-group-containing porous organic polymers in a sealed tube at high temperature. Fourier transform infrared and solid-state 13C CP/MAS NMR spectroscopy are utilized to characterize the possible structure of the obtained polymers. The highest Brunauer–Emmet–Teller specific surface area of the phenolic-resin porous organic polymers (PPOPs) is estimated to be 920 m2 g–1. The PPOPs exhibit a highest carbon dioxide uptake (up to 15.0 wt % (273 K) and 8.8 wt % (298 K) at 1.0 bar), and possess moderate hydrogen storage capacities ranging from 1.28 to 1.04 wt % (77 K) at 1.0 bar. Moreover, the highest uptake of methane for the PPOPs is measured as 4.3 wt % (273 K) at 1.0 bar.
Keywords: bisphenol A; carbon dioxide uptake; hydrogen storage; OH-containing; porous organic polymers